Islamic Religious Education Teachers' Strategies in Improving Students' Discipline of Fardhu Prayers at State Elementary School UPT 158 Mundan, Enrekang District - Irma; Wardah Hanafie Das; Muhammad Naim; Andi Abd. Muis; M. Nasir S (CV. Edujavare Publishing, 2026)
This study aims to describe and analyze in depth: (1) the strategies employed by Islamic Religious Education (PAI) teachers in improving students' obligatory prayer (shalat fardhu) discipline; (2) the effectiveness of those strategies; and (3) the supporting and inhibiting factors at UPT SD Negeri 158 Mundan, Enrekang Regency. A descriptive qualitative approach was adopted, with data gathered through participatory observation, in-depth semi-structured interviews, and documentation. Eight informants participated: the school principal, one PAI teacher, five class teachers (grades II–VI), and student representatives. Data analysis followed the Miles & Huberman model: data reduction, data display, and conclusion drawing/verification. Data credibility was ensured through source, method, and instrument triangulation. Findings reveal: (1) Applied strategies encompass six main components: habituating congregational prayer, teacher role modeling, positive reinforcement through rewards, personal approaches and intensive parental communication, integrating prayer values into instruction, and continuous evaluation/monitoring; (2) These strategies proved effective, evidenced by improved prayer punctuality, active congregational participation, and the growth of intrinsic worship awareness among students; (3) Supporting factors include institutional commitment, synergy between the PAI teacher and class teachers, parental support, and a conducive religious environment; inhibiting factors include limited student awareness, insufficient prayer habituation at home, peer influence, dense activity schedules, and limited prayer room capacity. The study concludes that obligatory prayer, within the elementary education context, functions not only as a ritual obligation but also as a medium for character formation—cultivating discipline, responsibility, and peace of mind—which positively influences students' learning attitudes and social life.